2000
DOI: 10.1016/s0016-7037(99)00355-5
|View full text |Cite
|
Sign up to set email alerts
|

Rutile/melt partition coefficients for trace elements and an assessment of the influence of rutile on the trace element characteristics of subduction zone magmas

Abstract: Abstract-Fractionation of some or all of the high field strength elements (HFSE) Nb, Ta, Zr, Hf, and Ti relative to other trace elements occurs in igneous rocks from convergent margins and in the average continental crust, and is generally attributed to a process occurring during subduction. The experimental partitioning of an extensive array of trace elements between rutile/melt pairs is presented which enables the effect of rutile during melting in subduction zones to be directly assessed. D Nb and D Ta are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
185
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(199 citation statements)
references
References 36 publications
(61 reference statements)
10
185
0
4
Order By: Relevance
“…This appears to indicate that more ilmenite melted locally, presumably reflecting its heterogeneous distribution within the metasomatic source assemblages. Note that rutile is unlikely to be the source of this additional HFSE contribution to some of the mela-aillikites, because it would have significantly increased the Nb-Ta content and Nb/Ta ratio of the melt (Foley et al, 2000;Klemme et al, 2005), which is not observed (Fig. 8).…”
Section: High Ti and Hfsementioning
confidence: 96%
“…This appears to indicate that more ilmenite melted locally, presumably reflecting its heterogeneous distribution within the metasomatic source assemblages. Note that rutile is unlikely to be the source of this additional HFSE contribution to some of the mela-aillikites, because it would have significantly increased the Nb-Ta content and Nb/Ta ratio of the melt (Foley et al, 2000;Klemme et al, 2005), which is not observed (Fig. 8).…”
Section: High Ti and Hfsementioning
confidence: 96%
“…The trace-element signatures of relative enrichment of light rare-earth elements (LREE) and large ion lithophile elements (LILE) to high-field-strength elements (HFSE) (i.e., high LREE/HFSE and LILE/ HFSE ratios) in magmas from arcs and orogenic belts are widely accepted as a consequence of enrichment processes induced by dehydration of subducted slabs (e.g., Arculus, 1994;Hunter and Blake, 1995;Turner et al, 1996;Foley et al, 2000;Tiepolo et al, 2000Tiepolo et al, , 2001. Under an oceanic continental subdirection system, such features are either ascribed to residual rutile and other titanate minerals that contain the HFSE during melting process or preferential enrichment of other incompatible elements to HFSE by slab-derived fluids in the source (e.g., Foley et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that eclogite melting in subduction zones may generate rutile-bearing residues that are residually-enriched in TITAN elements (e.g., . Experimental studies indicate that the TITAN elements are strongly partitioned into rutile during eclogite melting (Green and Pearson, 1986;Ryerson and Watson, 1987;Ayers, 1998;Stalder et al, 1998;Foley et al, 2000;Schmidt et al, 2004;Kessel et al, 2005), thereby generating positive TITAN anomalies in refractory, rutile-bearing slab residues that balance the depletion observed in subduction zone lavas.…”
Section: New Data and Observationsmentioning
confidence: 99%
“…Incompatible elements are largely lost to the overlying mantle during dehydration and melting of the eclogite portion of slabs. By contrast, titanium-rich phases, such as rutile, may preferentially sequester the TITAN elements in the mafic portion of the downgoing slab, balancing the depletion observed in subduction zone lavas (Green and Pearson, 1986;Ryerson and Watson, 1987;Brennan et al, 1994;Foley et al, 2000;Schmidt et al, 2004;Kessel et al, 2005). Refractory, rutile-bearing eclogites have been subducted in large quantities over geologic time, and may form a reservoir in the mantle that hosts the Earth's missing TITAN (McDounough, 1991;Rudnick et al, 2000).…”
Section: Introductionmentioning
confidence: 99%